Management manpower development: a vehicle for national development (2004)
"This study discusses the essence of management development as a national policy. No meaningful national development can take place without an appropriate management in place. This can be evolved through the installation and implementation of an enduring management development (training). This is because all the resources for national development and, indeed, for sectoral development are mobilized, organized, controlled, utilized and monitored by the manager. While management is an everyday phenomenon, the manager must acquire the skill, knowledge and competence through systematic management development programme. This study distinguishes management development from national development by discussing each of them in detail. It also makes distinction between training and development, stating that the former is a sub-set of the latter, and emphasizes that the differences lie in the fact that one has a duration, while the other is of continuous nature. While training may have a definite period, development is continuous training that dovetails from one form into another. The study fully examines the na ture of management and its relevance to national development. Thus, management development is a vehicle for realizing national development. Introduction"